Seed Extract of Psoralea corylifolia and Its Constituent Bakuchiol Impairs AHL-Based Quorum Sensing and Biofilm Formation in Food- and Human-Related Pathogens - Husain, Fohad Mabood; Ahmad, Iqbal; Khan, Faez Iqbal; Al-Shabib, Nasser A.; Baig, Mohammad Hassan; Hussain, Afzal; Rehman, Md Tabish; Alajmi, Mohamed F.; Lobb, Kevin A. (Frontiers in Cellular and Infection Microbiology, 2018)
The emergence of multi-drug resistance in pathogenic bacteria in clinical settings as well as food-borne infections has become a serious health concern. The problem of drug resistance necessitates the need for alternative novel therapeutic strategies to combat this menace. One such approach is targeting the quorum-sensing (QS) controlled virulence and biofilm formation. In this study, we first screened different fractions of Psoralea corylifolia (seed) for their anti-QS property in the Chromobacterium violaceum 12472 strain. The methanol fraction was found to be the most active fraction and was selected for further bioassays. At sub-inhibitory concentrations, the P. corylifolia methanol fraction (PCMF) reduced QS-regulated virulence functions in C. violaceum CVO26 (violacein); Pseudomonas aeruginosa (elastase, protease, pyocyanin, chitinase, exopolysaccharides (EPS), and swarming motility), A. hydrophila (protease, EPS), and Serratia marcescens (prodigiosin). Biofilm formation in all the test pathogens was reduced significantly (p ≤ 0.005) in a concentration-dependent manner. The β-galactosidase assay showed that the PCMF at 1,000 μg/ml downregulated las-controlled transcription in PAO1. In vivo studies with C. elegans demonstrated increased survival of the nematodes after treatment with the PCMF. Bakuchiol, a phytoconstituent of the extract, demonstrated significant inhibition of QS-regulated violacein production in C. violaceum and impaired biofilm formation in the test pathogens. The molecular docking results suggested that bakuchiol efficiently binds to the active pockets of LasR and RhlR, and the complexes were stabilized by several hydrophobic interactions. Additionally, the molecular dynamics simulation of LasR, LasR–bakuchiol, RhlR, and RhlR–bakuchiol complexes for 50 ns revealed that the binding of bakuchiol to LasR and RhlR was fairly stable. The study highlights the anti-infective potential of the PCMF and bakuchiol instead of bactericidal or bacteriostatic action, as the extract targets QS-controlled virulence and the biofilm.